Endogenous µ‐opioid receptor activity in the lateral and capsular subdivisions of the right central nucleus of the amygdala prevents chronic postoperative pain. Issue 1 (6th May 2021) - Cooper, Andrew H.; Hedden, Naomi S.; Corder, Gregory; Lamerand, Sydney R.; Donahue, Renee R.; Morales‐Medina, Julio C.; Selan, Lindsay; Prasoon, Pranav; Taylor, Bradley K.
Abstract: Tissue injury induces a long‐lasting latent sensitization (LS) of spinal nociceptive signaling that is kept in remission by an opposing µ‐opioid receptor (MOR) constitutive activity. To test the hypothesis that supraspinal sites become engaged, we induced hindpaw inflammation, waited 3 weeks for mechanical hypersensitivity to resolve, and then injected the opioid receptor inhibitors naltrexone, CTOP or β‐funaltrexamine subcutaneously, and/or into the cerebral ventricles. Intracerebroventricular injection of each inhibitor reinstated hypersensitivity and produced somatic signs of withdrawal, indicative of LS and endogenous opioid dependence, respectively. In naïve or sham controls, systemic naloxone (3 mg/kg) produced conditioned place aversion, and systemic naltrexone (3 mg/kg) increased Fos expression in the central nucleus of the amygdala (CeA). In LS animals tested 3 weeks after plantar incision, systemic naltrexone reinstated mechanical hypersensitivity and produced an even greater increase in Fos than in sham controls, particularly in the capsular subdivision of the right CeA. One third of Fos+ profiles co‐expressed protein kinase C delta (PKCδ), and 35% of PKCδ neurons co‐expressed tdTomato+ in Oprm1 Cre ::tdTomato transgenic mice. CeA microinjection of naltrexone (1 µg) reinstated mechanical hypersensitivity only in male mice and did not produce signs of somatic withdrawal. Intra‐CeA injection of the MOR‐selective inhibitor CTAP (300 ng) reinstated hypersensitivity in both male and female mice. We conclude that MORs in the capsular subdivision of the right CeA prevent the transition from acute to chronic postoperative pain. Abstract : Incision causes neuronal sensitization and acute postoperative pain. After injury resolves, endogenous µ‐opioid receptor (MOR) signaling in the central nucleus of the amygdala (CeA) suppresses latent pain sensitization. Inhibiting MOR signaling, either systemically or within the CeA, unmasks latent sensitization, leading to reinstatement of hypersensitivity.